D. -4
sq rt of 3x+28-8=x
add 8 to both sides
sq rt of 3x+28 = x+8
square both sides of the equation
3x + 28 = x^2 + 16x + 64
subtract x^2+16x+64 from both sides
group common terms
-13x-36-x^2=0
rearrange and put in quadratic form
x= -13 +/- sq rt of 13^2-4(1)(36) over 2(1)
subtract 169 by 144
x= -12 +/- sq rt of 25 over 2
solve for both sides
x = -13+5 over 2
=-4
x= -13-5 over 2
= -9
now plug in x
sq rt of 3(-4)+28 -8=-4
sq rt of 3(-9)+28 -8= -9
-4 = -4
but
-7 does not = -9
so -4 is the solution